Inovasi Seni Kreasi LUBA untuk Mendiversifikasi Cendera Mata Khas Kabupaten Klaten Jawa Tengah - Haryono, Tulus; Margana, Margana; Sugiarti, Rara (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
The Community Partnership Program (PKM) on creative art innovation "LUBA" was carried out in collaboration with UKM Rukun Makmur located in Klaten Central Java. There are centers of batik as well as lurik in the area but they arey have not been optimized. Therefore, this PKM activity focuses on new product innovation by combining lurik and batik crafts into innovative handicrafts called lurik batik (LUBA) which at the same time can act as a unique and iconic Klaten souvenir to support regional tourism development.There are several problems faced by UKM Rukun Makmur as partner. Based on these problems, this program aims to find solutions to all these problems by using several methods including counseling, discussing, training, and mentoring. The results of this PKM activities show that UKM Rukun Makmur has been able to increase their creativity to create designs, motifs, and varied color of lurik batik (LUBA) handicraft products.